Perilaku dalam Pengelolaan Lahan Pertanian di Kawasan Konservasi Daerah Aliran Sungai (DAS) Hulu Kabupaten Karanganyar - Hamzah Wijayanto Wijayanto; Sapja Anantayu; Agung Wibowo (AgriHumanis: Journal of Agriculture and Human Resource Development Studies, 2021)
Watershed has a purpose as a conservation area which needs to be performed to maintain environmental conditions from degradation. Beruk Village, Jatiyoso Sub-District is one of the watershed conservation areas. The Watershed which is administratively located in Karanganyar Regency is part of the Bengawan Solo watershed which has an important function as a water absorption area. This study aims is to find out to know the behavior of farmers in land management related to watershed conservation activitie. The method of research used is qualitative research with descriptive analysis. Deliberate location selection (purposive) in the village of Beruk District Jatiyoso Karanganyar Regency with consideration Beruk village is a red zone or disposed to to landslides so it is necessary to be considered in the management of land. Initial informant determination is done purposive sampling with key informants. This research is using triangulation method for data validation. The results showed that there is land management carried out by farmers in Beruk Village is adjusted to existing land conditions so as to protect the land from erosion. Land management conceded by farmers in Beruk Village in two ways, namely vegetative and mechanical land control.